Complications in Intermediate Uveitis: Prevalence, Time of Onset, and Effects on Vision in Short-Term and Long-Term Follow-Up. (3rd April 2019) - Sancho, Ligia; Kramer, Michal; Koriat, Adi; Eiger-Moscovich, Maya; Sharon, Yael; Amer, Radgonde
ABSTRACT: Purpose : To study the prevalence and time of onset of ocular complications in intermediate uveitis (IU) and to assess their effects on visual outcome in short-term and long-term follow-up. Methods : A retrospective cohort study of patients with IU who had a minimal follow-up of one year. Results : 96 patients (174 eyes, 70% females) were included with a mean age at presentation of 30 years. Children constituted 38% of all patients. Mean follow- up was 64.9 months. Pars planitis was the most common form followed by sarcoidosis and multiple sclerosis. Cystoid macular edema (CME), cataract, epiretinal membrane and posterior synechiae were the most prevalent complications. Posterior synechiae, band keratopathy, cataract and papillitis at presentation were associated with worse presenting visual acuity (VA). Of the late-onset complications, glaucoma/ocular hypertension (OHT) was the most significantly associated with worse long-term VA. Most sight-threatening complications (namely CME and glaucoma) were diagnosed at presentation while late complications predominantly affected the posterior segment and included among others peripheral retinal elevations, vasoproliferative tumors, and vitreous hemorrhage. Median LogMAR VA improved at short-term and long-term follow-up, from 0.2 to 0.1 (p<0.001). Subgroup analysis revealed significant VA improvement for eyes with all the different complications except for eyes with glaucoma/OHT. Conclusion : IU is a chronic low-grade uveitis that may be associated with protean early and late complications of the anterior or posterior segments or both. Optimal treatment regimens are imperative for the strict control of inflammation and proper management of complications thus allowing a favorable long-term prognosis.